Models of modernity: readings of selected novels of the late Weimar Republic - Sutton, Fiona (2001)
My thesis explores the various ways in which a small selection of novels published in 1931 depict and respond to a widespread sense of crisis during the final phase of the Weimar Republic, arguing that the authors foreground a powerful sense that modernity itself is in a state of crisis. I consider how the novels articulate diverse experiences of modernity, both within and beyond the metropolis and from different social, generational and gender perspectives. Moreover, I examine how the authors' evaluation of modernity is reflected in their use of formal and narrative techniques. Focusing upon Gabriele Tergit's Käsebier erobert den Kurfürstendamm, Hans Fallada's Bauern, Bonzen und Bomben and Irmgard Keun's Gilgi - eine von uns, I contend that the ambiguity and complexity of the authors' responses towards modernity were often flattened, simplified or ignored by reviewers in the politically polarized environment of the late Weimar Republic. This is partly the result of the debates about Neue Sachlichkeit which influenced the original reception of the novels and have continued to shape subsequent criticism. The novels themselves have often been labelled as classic examples of Neue Sachlichkeit. However, it is my contention that the novels also problematize some of the programmatic statements about this movement which circuated widely in the Weimar Republic. Therefore, I seek to re-examine the novels within the context of Weimar debates about modernity and Neue Sachlichkeit, as well as in the light of recent theoretical work in these areas. I also draw extensive comparisons and contrasts between the models of modernity foregrounded in Tergit's novel and Emile Durkheim's writings on anomie; in Bauern, Bonzen und Bomben and Ernst Bloch's Erbschaft dieser Zeit, and in Gilgi - eine von uns and Mikhail Bakhtin's Rabelais and His World.